(untitled) (International Journal of Language, Literacy and Translation, 2019)
The study of translation has transformed from its conventional method of written translation to a modern and complex process as a result of the expansion of information and communication technology, in addition to the globalisation of the media. The emergence of new translation field involves multimedia translation such as localisation, fansubbing, subtitling, surtitling, dubbing, to name but a few. In another perspective, translating for a specific audience, for example, children, is a communication between the audience as young viewers, and the adult as the translator. The goal of this study is to look into the approaches employed by the dubbing translator in tackling culturally linguistic references of sarcastic remarks, obscene/vulgar words, curse/abusive language, as well as negative visuals (obscene or violating) found in Malaysian children’s dubbed animated series (English-Malay). Three foreign children's animated series, Detective Conan and Crayon Shin Chan (Japan), and Spongebob SquarePants (US), dubbed into Malay, were chosen for the discussion, while Shavit’s theory of children’s translation rules and norms (1986) was selected to build the basis of the investigation and steer this descriptive-based study. The result demonstrated that sarcastic remarks, curse/abusive language, and violating images had occurred in the Detective Conan series while instilling the elements of politeness and suitability in translating and adapting the inappropriate dialogues. Obscene/vulgar words and images were mostly found in Crayon Shin Chan series, while curse/abusive/disgusting language and visuals were observed in SpongeBob SquarePants. However, text manipulation by means of domestication method had occurred in the Shin Chan’s dubbed dialogues, adding the flavour of local setting to the text. This paper came to the vital conclusion that it might be customary in some cultures to use direct language, while in other cultures this might be regarded offensive and obscene language, resulting in dominant and evident role of translators, in particular with children’s text translators.